Does the location of short-arm cast univalve effect pressure of the three-point mould?. (2020) - Montgomery, Blake K.; Perrone, Kenneth H.; Yang, Su; Segovia, Nicole A.; Rinsky, Lawrence; Pugh, Carla M.; Frick, Steven L.
Abstract: Purpose: Forearm and distal radius fractures are among the most common fractures in children. Many fractures are definitively treated with closed reduction and casting, however, the risk for re-displacement is high (7% to 39%). Proper cast application and the three-point moulding technique are modifiable factors that improve the ability of a cast to maintain the fracture reduction. Many providers univalve the cast to accommodate swelling. This study describes how the location of the univalve cut impacts the pressure at three-point mould sites for a typical dorsally displaced distal radius fracture. Methods: We placed nine force-sensing resistors on an arm model to collect pressure data at the three-point mould sites. Sensory inputs were sampled at 15 Hz. Cast padding and a three-point moulded short arm fibreglass cast was applied. The cast was then univalved on the dorsal, volar, radial or ulnar aspect. Pressure recordings were obtained throughout the procedure. Results: A total of 24 casts were analyzed. Casts univalved in the sagittal plane (dorsal or volar surface) retained up to 16% more pressure across the three moulding sites compared with casts univalved in the coronal plane (radial or ulnar border). Conclusion: Maintaining pressure at the three-point mould prevents loss of reduction at the fracture site. This study shows that univalving the cast dorsally or volarly results in less pressure loss at moulding sites. This should improve the chances of maintaining fracture reductions when compared with radial or ulnar cuts in the cast. Sagittal plane univalving of forearm casts is recommended.